The effect of hearing impairment on the production of prominences: The case of French-speaking school-aged children using cochlear implants and children with normal hearing. Issue 2 (April 2019) - Grandon, Bénédicte; Vilain, Anne; Gillis, Steven
This study explores the use of F0, intensity and duration in the production of two types of prominences in French: primary accent with duration as the main acoustic cue, and secondary accent with F0 and intensity as acoustic cues. These parameters were studied in 13 children using a cochlear implant (CI) and 17 children with a normal hearing (NH), aged 5 to 10 years. Words were recorded in two different tasks, word-repetition and picture-naming, to compare repetition of an audio model with spontaneous production. NH children were able to produce both types of prominences with duration on the one hand and the combination of F0 and intensity on the other hand, similar to what is described in the literature in French-speaking adults. NH children have a more stable use of prominences than CI children, who demonstrate more variability across tasks, more even-timed duration patterns and less modulation of F0 and intensity at vowel and word level than their NH peers.